2016
DOI: 10.1117/1.jbo.21.9.091312
|View full text |Cite
|
Sign up to set email alerts
|

Overview of diffuse optical tomography and its clinical applications

Abstract: Near-infrared diffuse optical tomography (DOT), one of the most sophisticated optical imaging techniques for observations through biological tissue, allows 3-D quantitative imaging of optical properties, which include functional and anatomical information. With DOT, it is expected to be possible to overcome the limitations of conventional near-infrared spectroscopy (NIRS) as well as offering the potential for diagnostic optical imaging. However, DOT has been under development for more than 30 years, and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 148 publications
0
140
0
7
Order By: Relevance
“…Diffuse optical imaging uses near-infrared light to probe tissue absorption and scattering properties up to several centimeters, making it very useful in cancers near the skin, including breast, head and neck, and melanoma. 79 One of its greatest advantages is the ability to noninvasively monitor tissue on a daily basis, without the need of an exogenous contrast agent. 80 Cerussi et al revealed that optical imaging has potential to clinically and longitudinally measure imaging biomarkers such as oxy- and deoxy-haemoglobin water and lipid, in response to targeted NAT, in addition to traditional chemotherapy.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…Diffuse optical imaging uses near-infrared light to probe tissue absorption and scattering properties up to several centimeters, making it very useful in cancers near the skin, including breast, head and neck, and melanoma. 79 One of its greatest advantages is the ability to noninvasively monitor tissue on a daily basis, without the need of an exogenous contrast agent. 80 Cerussi et al revealed that optical imaging has potential to clinically and longitudinally measure imaging biomarkers such as oxy- and deoxy-haemoglobin water and lipid, in response to targeted NAT, in addition to traditional chemotherapy.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…In practice, this procedure turns out to be exceedingly expensive for the application at hand. It is thus convenient to adopt a linearized perturbation approach, and we choose here, as it is customary in this field, the Rytov approximation …”
Section: Mathematical Models For the Dot Problemmentioning
confidence: 99%
“…t m , mean transit time; 1, 2, 3 denote detection times of photons traveling through the optical paths 1, 2, and 3 (inserted figure), respectively. Reproduced with permission from [113]. Copyright 2016 SPIE.…”
Section: Figurementioning
confidence: 99%